Packaged foods purchased on price promotion in Australia. (1st January 2023) - Davies, Tazman; Coyle, Daisy; Shahid, Maria; Pettigrew, Simone; Wu, Jason HY.; Marklund, Matti
Abstract: We examined the prevalence and magnitude of price promotions among purchases of packaged foods and beverages in Australia, as well as the contribution of price-promoted foods and beverages to apparent energy intake. We utilized grocery purchase data from a nationally representative panel of 10 000 households in 2019 (NielsenIQ Homescan panel), combined with a food nutrition dataset (FoodSwitch). Nutritional quality was defined using the Australian and New Zealand Health Star Rating (HSR), where products with an HSR <3.5 were classified as 'less healthy' and products with an HSR ≥3.5 were classified as 'healthy'. Apparent energy intake was expressed as the total energy content of all purchased products per day per capita. Price promotions were claimed by panel members. Overall, four-in-ten packaged products (41%) were purchased on price promotion. Compared to 'healthy' products, 'less healthy' products were more frequently purchased on price promotion (33% vs 48%, respectively, p < 0.001), but had a similar mean magnitude of price discount (both 22%). Low socio-economic status (SES) households consumed 18% more energy from 'less healthy' packaged products on price promotion than high SES households (1141 vs 970 kJ/day/capita, p < 0.001). In conclusion, restricting price promotions for 'less healthy' packaged foods and beverages could potentially improve diet quality and dietary inequalities in Australia.